Dampak Kebijakan Revitalisasi Pasar Tradisional Terhadap Kondisi Ekonomi Pedagang Pasar Tani Kota Bandar Lampung - M. Hadi Muktadir; Moneyzar Usman (Departement of Mathematics Education, 2023)
The essence of this study is to determine the effect of traditional market revitalization policies on the economic conditions of traders. One of the traditional markets in Bandar Lampung, namely Pasar Tani, is the location of this research. The sample in this study were 67 Farmers Market traders. In this study, questionnaires and interviews were used to collect data. The SPSS 25 regression analysis tool was used to analyze the primary data used in this study. Descriptive approach is the most effective method. According to the findings, data processing has a significant and beneficial effect on economic indicators such as the number of business segments and employment. However, there is one indicator, namely the increase in the income of Farmers Market traders which has decreased after the revitalization.